Field Oxygen Transfer Efficiency and Aeration Diffuser Calculations - Mott, Henry V. (McGraw-Hill's AccessEngineering., 2016)
Manufacturers' data for Standard Oxygen Transfer Efficiency (SOTE) versus gas flow rate per diffuser is used in combination with site-specific parameters to compute Actual (field) Oxygen Transfer Efficiency (AOTE). The AOTE and corresponding number of diffusers necessary to supply oxygen for a user-specified maximum Actual Oxygen Transfer Rate (AOTR) is determined. Then, once the number of diffusers is set, the AOTE and associated gas flow rate can be determined for any non-maximum AOTR. Computations employ standard atmospheric air as well as high-purity oxygen of user-specified oxygen content.